2018
DOI: 10.1080/24699322.2018.1495266
|View full text |Cite
|
Sign up to set email alerts
|

Is patient-specific pre-operative preparation feasible in a clinical environment? A systematic review and meta-analysis

Abstract: Technical difficulty of an operation is associated with patient and disease characteristics, indicating the necessity for surgeons to exercise patient-specific preparation. Such methods have been shown to be effective in the simulation suite, however, application in a real clinical environment has been sporadic. This systematic review attempts to answer if patient-specific preparation in challenging surgical procedures is feasible. A systematic review of OvidMedline, Embase and all Evidence Based Medicine revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…This review included both virtual and physical models used for either patient-specific preoperative planning or rehearsal. This study concluded that PsR is safe and feasible in concordance with this review [ 28 ].…”
Section: Discussionsupporting
confidence: 77%
“…This review included both virtual and physical models used for either patient-specific preoperative planning or rehearsal. This study concluded that PsR is safe and feasible in concordance with this review [ 28 ].…”
Section: Discussionsupporting
confidence: 77%
“…The development and growth of health care simulations can put an end to this model and provide an opportunity to rehearse high-risk, complex, and rare surgical procedures in a safe environment rather than on an actual patient. Yiasemidou et al [15] conducted a meta-analysis of studies comparing preoperative rehearsals to standard treatment with two distinct groups of patients and demonstrated that real procedures were performed quicker if preoperative rehearsal took place. However, the immediate clinical outcome was similar for practiced and non-practiced operations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the immediate clinical outcome was similar for practiced and non-practiced operations. Current evidence suggests that patient-specific preoperative preparation is feasible, safe, and decreases operational time [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Patient-specific preoperative planning enables surgeons to optimize approaches and anticipate difficulties, allowing for improved patient safety and decreased operative duration. 1 Cross-sectional medical imaging modalities such as computed tomography (CT) and magnetic resonance imaging (MRI) were first introduced in the 1970s, providing surgeons with the capacity to better diagnose and evaluate anatomic structures with 2-dimensional (2D) pictures. 2 , 3 However, these imaging techniques were unable to recreate complex 3-dimensional (3D) visualizations of anatomy as would be viewed in the operating room.…”
Section: Introductionmentioning
confidence: 99%